Penerapan Diagram Resetting EWMA Scheme (RES) dalam Mengontrol Coefficient Variation (CV) Kadar Asam Lemak Bebas - Bella Novia Syabandina; Suliadi (Bandung Conference Series: Statistics, 2023)
Abstract. One of the tools commonly used in monitoring the production process (Quality Control) is a control chart. The chart that is commonly used is the Shewhart control chart with the assumption that the average (μ) and standard deviation (